CRYPTOCURRENCIES IN THE VIEW OF ISLAMIC ECONOMICS - Ella Ariska; Nur Nafisah; Maryam Batubara (Sean Institute, 2022)
Technological developments and further knowledge then encouraged the discovery of new currencies such as e-money which are currently widely circulating including debit cards, smart cards and e-cash until what is being widely used is crypto money or cryptocurrency. Cryptocurrency itself is a technology with a database regulated by blockchain which is commonly used as a digital currency.Traditional money is official money issued by the government through Bank Indonesia in the form of banknotes or coins. Meanwhile, digital money is money stored in a computer chipset that can be transferred to another address (account) or withdrawn from an ATM.Bitcoin has the following criteria: (1) is digital (only a mathematical algorithm or does not have a form), (2) can be transacted among bitcoin users or merchant providers, (3) can be withdrawn in currency, (3) peer to peer transactions peer with internet network with verification from PT. Bitcoin or at Bitcoin ATMs, (4) transactions are subject to administration fees. In Islamic law digital money is included in muamalah, especially in buying and selling. From Law No. 7 of 2011 it can be concluded that bitcoin is not a legal tender, especially in Indonesia. Crypto currency or bitcoin has no intrinsic value as currency or other commodities such as gold, because the price is only influenced by supply and demand. Bitcoin also has no certainty of value (value),